ANALISIS KOMPETENSI DAN PENGEMBANGAN KARIR PEGAWAI DENGAN EMPLOYEE ENGAGEMENT SEBAGAI INTERVENING DALAM PENINGKATAN KINERJA APARATUR SIPIL NEGARA KECAMATAN DI WILAYAH KOTA DEPOK - Hidayat (2020)
The title of this research is the Competence analysis and the Career Development of the Employees by Employee Engagement as Intervening Aspect in the effort to develop the Performance of the State Civil Apparatus in Depok City region. This research has main purposes, among others: to identify impact of employee's competency and career development to the employee engagement and their performance with employee engagement variable as an intervening variable. The sample of the research is the State Civil Apparatus in Depok City region with the total sample of 82 employees. At the same time, PLS (Partial Least Square) was used for the data analysis. The result of this research shows that the competence of the State Civil Apparatus has no significant impact to their performance with coefficient pathway as 0.133 (p value 0.150 > 0,05) and State Civil Apparatus competency has no significant impact to the employee engagement with the coefficient pathway of 0.058 (p value 0,692 > 0.05). This result shows the necessity in competency enhancement for the State Civil Apparatus in Depok City sub-district. Based on analysis aspect, there is a necessity in developing communication skill competency, team work, time management, influencing communication, and problems solving ability. From the performance aspect, there is a necessity to enhance the outcome of work quality. Career development variable has a significant impact to the performance with the coefficient pathway of 0.283 (p value 0.022 < 0,05) and has significantly affected to the Employee Engagement with the coefficient pathway of 0.363 (p value 0,021 < 0.05). The good aspect implemented in the career development is a good career planning and development, employee assessment as well transparency in the employee career level. Employee Engagement variable has an impact to the employee performance with the coefficient pathway of 0.403 (p value 0,000 < 0.05). The various positive points of this variable are the enthusiasm, spirit and passion of the State Civil Apparatus in Depok City to work. However, there is necessity to increase a amenities and convenience in the organization as well as encourage and embolden the participation/involvement for the success of the organization. The success of the organization is not the individual success but the success of the State Civil Apparatus of Depok City sub-district. Keywords: Competence, Career Development of the Employees, Employee Engagement, Performance of Employees.